Karyological analysis and NOR polymorphism of phayre’s langur, Trachypithecus phayrei crepuscula (Primate, Colobinae) in Thailand - Krit Pinthong (2018)
© 2017, Archana Sharma Foundation of Calcutta. Karyological analysis of Phayre’s langur (Trachypithecus phayrei crepuscula) at Songkhla Zoo, Thailand has been reported in this present article. Conventional staining, GTG-banding, and high-resolution technical analysis were carried out on standard whole blood T-lymphocyte culture from 4 sp ecimens of T. phayrei crepuscula. The results showed that the diploid number is 2n = 44 and the fundamental number is 88 in both male and female. The autosomes consisted of 6 large metacentric, 10 large submetacentric, 2 large acrocentric, 6 medium metacentric, 14 medium submetacentric, 2 small submetacentric, and 2 small acrocentric chromosomes. The X chromosome is the large submetacentric chromosome, while the Y chromosome is medium metacentric chromosome. From GTG-banding and using high-resolution techniques, the numbers of bands and locations in T. phayrei crepuscula are 224 and 259, respectively, and each chromosome pair could be clearly differentiated. In addition, the long arm of subcentromeric chromosome pair 17 showed clearly observable nucleolar organizer regions/NORs. This is the first report on polymorphism of NORs in T. phayrei crepuscula. Thus the results indicated that a heteromorphic chromosome pair with different sizes of NORs is present for chromosome pair 17 (17a 17b) in both male and female animal. The results provide useful information for further cytogenetic study of this species. The karyotype formula could be deduced as: 2n(44)=L6m+L10sm+L2a+M6m+M14sm+S2sm+S2a+2 Sex-chromosomes.